2020
DOI: 10.3390/min10010074
|View full text |Cite
|
Sign up to set email alerts
|

Distribution Characteristics and Influencing Factors of Uranium Isotopes in Saline Lake Waters in the Northeast of Qaidam Basin

Abstract: Four saline lakes in the northeast of Qaidam Basin were selected to explore the distribution characteristics and influencing factors of uranium isotopes in lake waters with high evaporation background. The 238U concentration and the activity ratios of 234U/238U ([234U/238U]AR) showed that there was no significant change in the same lake, but there was a certain degree of difference in the distribution between different lakes. We found that aqueous 238U concentration within a certain range increased with an inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 47 publications
2
13
0
Order By: Relevance
“…The water chemistry results of each sampled lake are presented in Table 4, including the aqueous 238 U concentration and the [ 234 U/ 238 U] AR . Aqueous 238 U concentrations of the freshwater lakes in the northeastern part of the Qaidam Basin were generally low, which is consistent with the results of previous analyses of lake water samples collected in June, July and the beginning of December without ice coverage (Zhao et al, 2020). The 238 U concentration of ice from the five sampled lakes were less than that of water under the ice, except for samples from QHH.…”
Section: Distribution Of Uranium Isotopes In Lake Ice and Waters In The Qinghai Region And The Northeastern Part Of Qaidam Basinsupporting
confidence: 88%
See 4 more Smart Citations
“…The water chemistry results of each sampled lake are presented in Table 4, including the aqueous 238 U concentration and the [ 234 U/ 238 U] AR . Aqueous 238 U concentrations of the freshwater lakes in the northeastern part of the Qaidam Basin were generally low, which is consistent with the results of previous analyses of lake water samples collected in June, July and the beginning of December without ice coverage (Zhao et al, 2020). The 238 U concentration of ice from the five sampled lakes were less than that of water under the ice, except for samples from QHH.…”
Section: Distribution Of Uranium Isotopes In Lake Ice and Waters In The Qinghai Region And The Northeastern Part Of Qaidam Basinsupporting
confidence: 88%
“…They found that one end of the lake had a low uranium content and low salinity, while the other end had the opposite. The U content measured by Zhao et al (2020) in several saline lakes and our unpublished salt lakes shows the 238 U concentration varied with the range of 12.6-200 μg/L. Other studies have also shown that the U content of lakes water varies directly with TDS (salinity) and pH, the latter of which is partially controlled by evaporation and/or other secondary concentration pathways (Osmond et al, 1974;Borole et al, 1982;Yadav and Sarin, 2009;Zhang et al, 2019;Chen et al, 2020;Zhao et al, 2020).…”
Section: U Isotope Variations and The Controlling Factors In The Saline Lake Systemmentioning
confidence: 68%
See 3 more Smart Citations